IL-10 Produced by Trophoblast Cells Inhibits Phagosome Maturation Leading to Profound Intracellular Proliferation of Salmonella enterica Typhimurium - Nguyen, Tina (2013)
INTRODUCTION: Salmonella enterica Typhimurium (ST) is a phagosomal pathogen that can infect placental trophoblast cells leading to abortion and severe maternal illness. It is unclear how the trophoblast cells promote profound bacterial proliferation. METHODS: The mechanism of internalization, intracellular growth and phagosomal biogenesis in ST-infected human epithelial (HeLa), macrophage (THP-1) and trophoblast-derived cell lines (JEG-3, BeWo and HTR-8) was studied. Specific inhibitors were used to block bacterial internalization. Phagosomal maturation was determined by confocal microscopy, western-blotting and release of lysosomal β-galactosidase by infected cells. Bacterial colony forming units were determined by plating infected cell lysates on agar plates. RESULTS: ST proliferated minimally in macrophages but replicated profoundly within trophoblast cells. The ST-∆invA (a mutant of Salmonella pathogenicity island-1 gene effector proteins) was unable to infect epithelial.cells, but was internalized by scavenger receptors on trophoblasts and macrophages. However, ST was contrastingly localized in early (Rab5(+)) or late (LAMP1(+)) phagosomes within trophoblast cells and macrophages respectively. Furthermore trophoblast cells (unlike macrophages) did not exhibit phagoso-lysosomal fusion. ST-infected macrophages produced IL-6 whereas trophoblast cells produced IL-10. Neutralizing IL-10 in JEG-3 cells accelerated phagolysomal fusion and reduced proliferation of ST. Placental bacterial burden was curtailed in vivo in anti-IL-10 antibody treated and IL-10-deficient mice. DISCUSSION: Macrophages phagocytose but curtail intracellular replication of ST in late phagosomes. In contrast, phagocytosis by trophoblast cells results in an inappropriate cytokine response and proliferation of ST in early phagosomes. CONCLUSION: IL-10 production by trophoblast cells that delays phagosomal maturation may facilitate proliferation of pathogens in placental cells.